PENGEMBANGAN BAHAN AJAR DIGITAL BERBASIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PADA PEMBELAJARAN MATEMATIKA (Bahan Ajar Digital Interaktif pada Materi Pertidaksamaan Nilai Mutlak Linear Satu Variabel) - Artisa Indariani; Surya Amami Pramuditya; Siska Firmasari (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2018)
This research motivated by the low of students’ mathematical problem-solving ability and the utilization of learning media based on technology that was not maximum. Preparation of learning materials in the form of the interactive digital module was one of the ways can overcome that problem. The method that used in this research was RnD with the design model ADDIE that was analysis, development of implementation design and evaluation with the restrictions of not doing the implementation stage. The instrument of collecting data in this research was the form of validation and the form of practicalities of the user senior high school students that has to get the material of linear inequality absolute value. The data that was taken though with statistics descriptive way. The validation result of the digital module gets ratings in the amount of 83,33% from media expert and 85,57% from a material expert. This interactive digital module was decent to use and very practical with the average percentage for students’ high cognitive ability 88,77%, medium 89,49%, and low 82,97%. Whereas the other user that was mathematics teacher give the percentage 84,78% so, according to them this digital module was very practical.